The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1098/rspa.2014.0216
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modelling of magnetic shape memory alloys with discrete and continuous symmetries

Abstract: A free energy-based constitutive formulation is considered for magnetic shape memory alloys. Internal state variables are introduced whose evolution describes the transition from reference state to the deformed and transformed one. We impose material symmetry restrictions on the Gibbs free energy and on the evolution equations of the internal state variables. Discrete symmetry is considered for single crystals, whereas continuous symmetry is considered for polycrystalline materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We refer the reader to Haldar and Lagoudas [26] where they discuss the single crystal anisotropic behavior.…”
Section: ( )mentioning
confidence: 99%
“…We refer the reader to Haldar and Lagoudas [26] where they discuss the single crystal anisotropic behavior.…”
Section: ( )mentioning
confidence: 99%
“…The permeability of the free space is μ 0 , and the density of the material is ρ. A detailed discussion on the construction of the Gibbs free potential for MSMAs and constitutive responses, including discrete crystalline symmetry restrictions, could be found in [15,31]. We further consider the evolution equations for the reorientation strain and the mixing energy as…”
Section: (A) Magnetic Shape Memory Alloy Constitutive Responsesmentioning
confidence: 99%
“…In the reorientation mechanism, the variants have different preferred directions of magnetization and the magnetic field is applied to select certain variants, which results in the macroscopic shape change. We follow Haldar & Lagoudas [15] among the many other available modelling approaches which aim to capture the phenomenology of the material responses.…”
Section: Introductionmentioning
confidence: 99%
“…3 Elaborate experimental methods are needed to analyze coupled multi-field e↵ects and, therefore, such studies are rarely reported in the literature. [6][7][8][9] Multi-field property measurements are increasingly sought after to understand the coupled material behaviors 3 and to calibrate constitutive models, [10][11][12][13][14] and thereby improve the active material response.…”
Section: Introductionmentioning
confidence: 99%